Hoyosella suaedae sp. nov., a novel bacterium isolated from rhizosphere soil of Suaeda aralocaspica (Bunge) Freitag & Schütze. Issue 11 (30th November 2021) - Liu, Dan-Feng; Chen, Shao-Qi; Wang, Hong-Fei; Xie, Yuan-Guo; Gao, Rui; Song, Jie-Qiong; Gao, Yan-Li; Xiao, Min; Li, Qiu-Li; Li, Wen-Jun
Abstract : A Gram-stain-positive, non-motile and coccus-shaped bacterium, designated strain LNNU 331112 T, was isolated from the composite rhizosphere soil of the halophyte Suaeda aralocaspica (Bunge) Freitag and Schütze, which was collected in Xinjiang, north-west China. Growth occurred at 10–45 °C, pH 6.0–11.0 and in the presence of 0–10 % NaCl (w/v). Phylogenetic analysis based on the 16S rRNA gene sequence suggested that strain LNNU 331112 T belonged to the genus Hoyosella and showed 95.6, 95.5 and 95.4 % sequence similarities to Hoyosella altamirensis DSM 45258 T, Hoyosella subflava CGMCC 4.3532 T and Hoyosella rhizosphaerae CGMCC 1.15478 T, respectively. The estimated digital DNA–DNA hybridization relatedness values between strain LNNU 331112 T and the type strains of H. altamirensis DSM 45258 T, H. subflava CGMCC 4.3532 T and H. rhizosphaerae CGMCC 1.15478 T were 18.9, 19.3 and 18.3 %, respectively. The average nucleotide identity values between strain LNNU 331112 T and H. altamirensis DSM 45258 T, H. subflava CGMCC 4.3532 T and H. rhizosphaerae CGMCC 1.15478 T were 72.6, 72.7 and 72.3 %, respectively. The genome sequence of strain LNNU 331112 T showed 69.0–72.3 % average amino acid identity values in comparison with the related genome sequences of three validly published Hoyosella species. The genome of strain LNNU 331112 T was 3.47 Mb, with a DNA G+C content of 68.4 mol%. A total of 3182 genes were identified as protein-coding in strain LNNU 331112 T . Genomic analysis revealed that a number of genes involved in osmotic pressure regulation, intracellular pH homeostasis and potassium (K + ) uptake protein were found in strain LNNU 331112 T . The predominant menaquinones were MK-8 (44.6 %) and MK-7 (55.4 %), which differentiated strain LNNU 331112 T from other three recognized Hoyosella species. Major fatty acids (>10 %) were C17 : 1  ω8 c (33.8 %), C16 : 0 (23.3 %), C17 : 0 (12.8 %) and summed feature 3 (12.9 %), which also clearly separated strain LNNU 331112 T from three recognized Hoyosella species. The polar lipid profile of strain LNNU 331112 T included diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol, phosphatidylinositol, one unidentified glycolipid, one unidentified phospholipid and two unidentified lipids. According to the results of phenotypic, chemotaxonomic and phylogenetic analyses, strain LNNU 331112 T is considered to represent a novel species of the genus Hoyosella, for which the name Hoyosella suaedae sp. nov. is proposed. The type strain is LNNU 331112 T (=KCTC 39808 T =CGMCC 1.17107 T =DSM 103463 T ).